2007
DOI: 10.1111/j.1750-2659.2007.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza and poultry workers, Peru, 2006

Abstract: Background  Currently numerous countries in Asia, Africa and Europe are encountering highly pathogenic avian influenza (AI) infections in poultry and humans. In the Americas, home of the world’s largest poultry exporters, contingency plans are being developed and evaluated in preparation for the arrival of these viral strains. Objectives  With this cross‐sectional study, to our knowledge the first in its kind in Central or South America, we sought to learn whether Peruvian poultry workers had evidence of previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Although the results could be attributed at least partially to the presence of an undetectable amount of genomic RNA, based upon the sensitivity of the test, our findings demonstrated that no RNA genome of influenza A viruses was present in the samples under study. Despite H1 and H3 are most currently subtypes in human population and there is limited information on the prevalence of these two subtypes among birds, but some previous studies have been reported presence of antibodies to H1N1 and H3N2 viruses in wild and domestic birds in Brazil (16). Our study showed a high seropositivity of 57.7% against H1 subtype and also 88.75% against H3 subtype.…”
Section: Discussionsupporting
confidence: 57%
“…Although the results could be attributed at least partially to the presence of an undetectable amount of genomic RNA, based upon the sensitivity of the test, our findings demonstrated that no RNA genome of influenza A viruses was present in the samples under study. Despite H1 and H3 are most currently subtypes in human population and there is limited information on the prevalence of these two subtypes among birds, but some previous studies have been reported presence of antibodies to H1N1 and H3N2 viruses in wild and domestic birds in Brazil (16). Our study showed a high seropositivity of 57.7% against H1 subtype and also 88.75% against H3 subtype.…”
Section: Discussionsupporting
confidence: 57%
“…including H4 viruses (Kayali et al, 2010(Kayali et al, , 2011Ortiz et al, 2007). Therefore, attention should be paid to the potential threats to humans posed by H4 LPAIVs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, two H4N6 LPIAV strains isolated from pigs in Canada in 1999 possess Q226L and G228S substitutions in their HA sequences, implying the adaptation for human receptor preference (Bateman et al, 2008;Karasin et al, 2000). In addition, seroepidemiological studies reveal that poultry-exposed populations, including poultry farmers, workers, and veterinarians, are at a greater risk of infection with zoonotic IAVs, including H4 viruses (Kayali et al, 2010(Kayali et al, , 2011Ortiz et al, 2007). These results clearly implicate the potential threat posed by H4 viruses to public health.…”
Section: Accession Numbersmentioning
confidence: 99%
“…Antibody responses to AIV strains were detected by use of a microneutralization (MN) assay 58 (Table 1). We screened H5N2, H7N2, and H9N2 in 2008, H5N2 and H7N3 in 2009, and H5N2, H7N2, and pH1N1 in 2010 to test for avian and swine influenza co-infection.…”
Section: Objectivesmentioning
confidence: 99%